Forensic science : Fundamentals & investigations - Bertino, Anthony J.; Bertino, Patricia Nolan (Boston, MA : Cengage Learning, 2016)
With today's popular television programs about criminal justice and crime scene investigation and the surge of detective movies and books, students often have a passion for exploring forensic science. Now you can guide that excitement into a profitable learning experience with the help of the innovative, new FORENSIC SCIENCE: FUNDAMENTALS AND INVESTIGATIONS, 2E. This dynamic, visually powerful text has been carefully crafted to ensure solid scientific content and an approach that delivers precisely what you need for your high school course. Now an established best-seller, FORENSIC SCIENCE: FUNDAMENTALS AND INVESTIGATIONS, 2E offers a truly experiential approach that engages students in active learning and emphasizes the application of integrated science in your course. Student materials combine math, chemistry, biology, physics, and earth science with content aligned to the National Science Education Standards, clearly identified by icons. This book balances extensive scientific concepts with hands-on classroom and lab activities, readings, intriguing case studies, and chapter-opening scenarios. The book's exclusive Gale Forensic Science eCollection database provides instant access to hundreds of journals and Internet resources that spark the interest of today's high school students. The new edition includes one new chapter on entomology and new capstone projects that integrate the concepts learned throughout the text. Comprehensive, time-saving teacher support and lab activities deliver exactly what you need to ensure that students receive a solid, integrated science education that keeps readers at all learning levels enthused about science. FORENSIC SCIENCE: FUNDAMENTALS AND INVESTIGATIONS, 2E sets the standard in high school forensic science ... case closed. --
1. Observational Skills. -- 2. Crime Scene Investigation & Evidence Examination. -- 3. The Study of Hair. -- 4. A Study of Fibers and Fabrics. -- 5. Forensic Botany. -- 6. Fingerprinting. -- 7. DNA Profiling. -- 8. Blood & Blood Spatter. -- 9. Forensic Toxicology. -- 10. Handwriting Analysis, Forgery, and Counterfeiting. -- 11. Forensic Entomology -- 12. Death: Meaning, Manner, Mechanism, Cause and Time. -- 13. Soil Examination. -- 14. Forensic Anthropology. -- 15. Glass Evidence. -- 16. Casts and Impressions. -- 17. Tool Marks. -- 18. Ballistics. -- Capstone Projects. -- Project 1 Personal Evidence Portfolio. -- Project 2 Mock Crime Scene Development and Processing. -- Project 3 Analysis of a Forensic Science TV Show Diving. -- Project 4 Forensic Dumpster Diving. -- Project 5 Physical Evidence Case Studies. -- Project 6 Forensic Science Career Exploration. -- Project 7 Landmark Cases. -- Project 8 How reliable is the Evidence. -- Project 9 (new) Forensic Grave site Dig. -- Glossary -- Appendices -- Sine Table -- Tangents Table -- Bone Measurements Table -- Celsius-Fahrenheit Conversion Table. -- Index.
Copywrite 2016, 2012 Cengage Learning ; National Geographic Learning; South-Western Cengage Learning.
The Standard in High School Forensic Science--Backcover.
Includes bibliographical references and index.
Keywords: Forensic sciences -- Textbooks; Criminal investigation -- Textbooks; Criminal investigation -- Study and teaching; Forensic sciences -- Study and teaching